2014
DOI: 10.1016/j.physa.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Barrier properties of -mer packings

Abstract: This work discusses numerical studies of the barrier properties of k-mer packings by Monte Carlo method. The studied variants of regular and non-regular arrangements on a square lattice included models of random sequential adsorption (RSA) and random deposition (RD). The discrete problem of diffusion through the bonds of a square lattice was considered. The k-mers were perfectly oriented perpendicular to the diffusion direction and blocked certain fraction of bonds f b against diffusion. The barrier efficiency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The implication of these results is significant. While the BIF of the aligned flake composite shows a near-parabolic increase with (αϕ), as would be expected from theory, 8,9 randomly oriented composites deviate from that behavior and, instead, achieve BIF values which seem to plateau for increasing (αϕ) at a fraction of the BIF of the corresponding aligned composite. A similar result is implicit in the work of Lusti et al.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The implication of these results is significant. While the BIF of the aligned flake composite shows a near-parabolic increase with (αϕ), as would be expected from theory, 8,9 randomly oriented composites deviate from that behavior and, instead, achieve BIF values which seem to plateau for increasing (αϕ) at a fraction of the BIF of the corresponding aligned composite. A similar result is implicit in the work of Lusti et al.…”
Section: Resultssupporting
confidence: 69%
“…When the flakes are randomly placed and well aligned, the predicted barrier efficiency improvement ranges from being ∼(αϕ) in dilute systems, where (α) is the aspect ratio and (ϕ) the flake volume fraction, to being ∼(αϕ) 2 in more concentrated dispersions. 6,8,9 Considering the usually large flake aspect ratio, significant barrier property improvement can be achieved by adding a small amount of filler. Computational and experimental studies are in agreement with these predictions.…”
Section: Introductionmentioning
confidence: 99%
“…This oversimplified approximation was used only for qualitative estimations of the barrier properties of a dense layer on the drying rate. In the general case, the barrier properties can depend on details of the structure, density and thickness of the layer of sticks oriented along the evaporating interface (see [46] and references therein for the details). The transition from the isotropic to the ordered nematic phase was observed at ρ ≈ 7 [23,24].…”
Section: Computational Modelmentioning
confidence: 99%
“…It is known that incorporation of such fillers aligned perpendicular to the direction of macroscopic diffusion is very effective in increasing the barrier properties. Both theoretical results and computational studies have shown that, for flakes aligned perpendicular to the direction of macroscopic diffusion, the improvement in the Barrier Improvement Factor (BIF) ranges from being ~(αφ) in dilute systems, where (α) is the aspect ratio and (φ) the volume fraction of the flakes, to being ~(αφ) 2 in more concentrated dispersions [3][4][5][6][7]. When the orientation of the flakes deviates from perfect alignment, it is known that the BIF decreases; however no universally accepted models to predict this effect exist and only limited computational results have been presented, with the exception of the recent studies of [7][8][9].…”
Section: Introductionmentioning
confidence: 99%